Laser assisted orthodontic tooth movement in Saudi population: a randomized clinical trial. (Bangladesh Journal of Medical Science, 2019)
Objectives: This study aimed to assess laser assisted orthodontic tooth movement (OTM) among subjects undergoing fixed orthodontic treatment (FOT) of four different treatment modalities (TM).Materials and Methods: Following consort flow diagram, a total of 32 subjects randomly allocated in to 4 different group based on TM. Group A (GA): 8 subjects, FOT with self-ligating bracket (SLB) + low laser irradiation (LLLI), Group A (GB): 8 subjects, FOT with self-ligating bracket + Non-LLLI, Group C (GC): 8 subjects, FOT with conventional bracket (CB) + low laser irradiation (LLLI), Group D (GD): 8 subjects, FOT with CB + Non-LLLI.Results: Clinical photographs and diagnostic CBCT has been taken. Clinical observation of OTM, baseline, 1-day and 28-day afterFOT in all TM groups has been assessed by single calibrated specialist. Among 4 TM groups, best OTM results observed in GA and the lesser OTM observed in GD.Conclusion: Among all 4 TM groups,1-month after FOT GA revealed promising benefit in relation to OTM.Bangladesh Journal of Medical Science Vol.18(2) 2019 p.385-390